English English - Hanifah, Nurdinah; Djuanda, Dadan; Aeni, Ani Nur (International Conference on Elementary Education, 2024)
Assessment is a tool that chronologically helps teachers monitor students. Therefore, assessment should be an inseparable part of learning. Assessment essentially focuses on assessing student learning processes. Assessment not only reveals the concepts that have been achieved, but also about the development process of how a concept was obtained. This research was designed as a descriptive research with a qualitative approach. Data collection techniques use interviews. The research results concluded that teachers experienced difficulties in carrying out diagnostic, formative and summative assessments, especially in determining assessments that were appropriate to the learning objectives to be achieved, due to the many types or forms of assessment such as presentations, projects, products, oral, written and so on.